The Influence of the Principal’s Role on the Pedagogic Competence of State Junior High School Teachers - Lestari, Hendang Zeta; Nurkolis, Nurkolis; Murniati, Ngurah Ayu Nyoman (Graduate Program Magister Manajemen Pendidikan, 2025)
This study aims to determine the extent of the influence of the principal’s role on the pedagogical competence of junior high school teachers in Rembang District, Rembang Regency. The population in this study was 209 junior high school teachers in Rembang District, Rembang Regency. The research sample was 137 teachers using a proportional random sampling technique. The data collection technique used was a questionnaire. The data processing technique used a simple regression test. The results of the study showed that there was a positive and significant influence of the principal’s role on teacher pedagogical competence, which was stated by the regression equation Y = 44.549 + 0.646X and a contribution of 64.0%. It is recommended for teachers to create a safe and comfortable learning environment for students by creating an atmosphere that supports learning activities. Principals are advised to improve their ability to manage school administration.